Specialist paediatric palliative care for children and young people with cancer: A mixed-methods systematic review. (June 2020) - Taylor, Johanna; Booth, Alison; Beresford, Bryony; Phillips, Bob; Wright, Kath; Fraser, Lorna
Background: Specialist paediatric palliative care services are promoted as an important component of palliative care provision, but there is uncertainty about their role for children with cancer. Aim: To examine the impact of specialist paediatric palliative care for children and young people with cancer and explore factors affecting access. Design: A mixed-methods systematic review and narrative synthesis (PROSPERO Registration No. CRD42017064874). Data sources: Database (CINAHL, Cochrane Database of Systematic Reviews, Embase, MEDLINE, PsycINFO) searches (2000–2019) identified primary studies of any design exploring the impact of and/or factors affecting access to specialist paediatric palliative care. Study quality was assessed using The Mixed Methods Appraisal Tool. Results: An evidence base of mainly low- and moderate-quality studies ( n = 42) shows that accessing specialist paediatric palliative care is associated with less intensive care at the end of life, more advance care planning and fewer in-hospital deaths. Current evidence cannot tell us whether these services improve children's symptom burden or quality of life. Nine studies reporting provider or family views identified uncertainties about what specialist paediatric palliative care offers, concerns about involving a new team, association of palliative care with end of life and indecision about when to introduce palliative care as important barriers to access. There was evidence that children with haematological malignancies are less likely to access these services. Conclusion: Current evidence suggests that children and young people with cancer receiving specialist palliative care are cared for differently. However, little is understood about children's views, and research is needed to determine whether specialist input improves quality of life.